Partial root zone drying application in the propagation of vegetable in Northern Nigeria (2012)
"This study compares the response of Amaranthus candatus vegetable to root-to-shoot signals of soil drying and assesses applicability of the use of partial root zone drying (PRD) technique in increasing water-use efficiency. From a completely block randomized design, seeds were grown on three plots with each having three replicates. Three treatments were compared: half of the root system watered and half droughted by delivering 50% less crop water requirement (CWR) per irrigation depicted as 50%PRD; both halves of the root system received water application of 50% less crop water requirement per irrigation (50%CWR); while in the control treatment, both halves received 100% crop water requirement (100%CWR). The wetted and dried sides of the root system of 50%PRD were alternated on a 7-day cycle throughout experimental period. Effects of the differences in water-use on growth parameters, such as plant height, stem girth; number of leaves and leaf area were examined. Weights at harvest and root-to-shoot ratios were also compared. Drying half of the root system caused marked declines in all growth parameters in 50%CWR but only slight declines in 50%PRD. Since the main effect of water stress on Amaranthus is yield reduction, achieving better yields requires an optimum water supply from planting until ripening. Average edible wet weights (yields) of the 50%PRD and 50%CWR water applications when compared with the control were 81% and 25% respectively. The higher yield in 50%PRD may be attributed to high stomata sensitivity to drought signaling, as indicated by relatively low root to shoot ratio of 0.33. This lower ratio for 50%PRD treatment, compared to 50%CWR and 100%CWR with 0.40 and 0.66 values, was an indication of healthier and more profitable plants in 50%PRD because the decrease came from a greater shoot size."